Aid distribution and co-operation in unequal communities - Ben d' Exelle; Marrit Van den Berg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
We study the influence of economic inequality on co-operation and aid distribution in community-based development schemes. For this, we organized a field experiment in which community members contributed to a collective effort to attract aid. We find that devolving aid distribution to community representatives increases the aid attracted, but that this benefits community representatives only. At the same time, however, community representatives do take fairness considerations into account. They give higher aid shares to poorer community members and lower shares to low contributors. Moreover, representatives with lower relative wealth or who contribute relatively more keep higher aid shares.
Keywords: C93; D31; D70; 330; collective action; aid distribution; experiment; Nicaragua